Philosophical and social foundations of the internationalisation of higher sports education in China - Guo, Jimao (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article identifies and analyses the ideological and social foundations of the internationalisation of higher sports education in China, which is the basis for building a modern model of Chinese sports education. In the context of the specifics of the perception of physical education and sports in the national tradition, the article explores the socio-philosophical ideas and attitudes of traditional Chinese philosophy, value preferences of modern Chinese society, emphasises the importance of promoting national sports as an significant element of higher sports education and physical education in general. Based on the study of theoretical sources and practical work the strategy for enhancing the reputation of national Chinese sports and higher sports education in the international arena is analysed. The role of the massification of physical education and sports as a social basis for the internationalisation of higher sports education in China is considered.